Arlington Road - Mark Pellington; Hope, Davis; Joan Cusack; Mason Gamble; Robert Gossett; Spencer Treat Clark; Tim Robbins; Jeff Bridges (USA Arlington Road Productions Corporation, 1999)
Widowed when his FBI agent wife is killed in an FBI anti-terrorist operation gone wrong, a college professor (Bridges) becomes increasingly obsessed with the culture and sub-society of these dangerous groups. The arrival of new neighbors (Robbins, Cusack), gives him new spirit, as they are gregarious and friendly, with two children (Gamble, Green) that his son (Clark) can be friends with. He is even beginning to see another woman (Davis). However, he begins to suspect something is odd about the neighbors, something about the way they don't want him to see certain parts of the house, or a set of blueprints they have there. Are his neighbors terrorists... or is the stress of losing his wife merely driving him past the point of paranoia?
A college professor begins to suspect that his neighbour is a terrorist.
Ehren Kruger
Languages: English, Spanish
Subtitle: English
Keywords: Drama; Mystery; Thriller